Figuras femininas e fronteiras sociais na poética de Manoel de Barros - Rodrigues, Rauer Ribeiro [UNESP] (Pontifícia Universidade Católica do Rio Grande do Sul (PUC-RS), 2011)
We contemplated concerning the borders in the social relationships, verifying that way the speech poetic internalizes the moral conventions and it fastens identities when proposing the alterity as a one other radically different. We studied the woman's representation in the poetry of Manoel de Barros, in the grandmother's figures, of the mother, of the women of the people and of the prostitutes. We verified the way as the women are figured and the function that they carry out in the universe of poetic's Barros.
Feminine figures and frontiers social in the poetic of Manoel de Barros
Keywords: History; Brazilian literature; Poetry